The XXL Survey. XLII. The LX − σv relation of galaxy groups and clusters detected in the XXL and GAMA surveys. Issue 1 (2nd February 2022) - Giles, P A; Robotham, A; Ramos-Ceja, M E; Maughan, B J; Sereno, M; McGee, S; Phillipps, S; Iovino, A; Turner, D J; Adami, C; Brough, S; Chiappetti, L; et al.
ABSTRACT: The XXL Survey is the largest homogeneous survey carried out with XMM-Newton . Covering an area of 50 deg 2, the survey contains several hundred galaxy clusters out to a redshift of ≈2, above an X-ray flux limit of ∼6 × 10 −15 er g cm −2 s −1 . The GAMA spectroscopic survey of ∼300 000 galaxies covers ≈286 deg 2, down to an r-band magnitude of r < 19.8 mag. The region of overlap of these two surveys (covering 14.6 deg 2 ) represents an ideal opportunity to study clusters selected via two independent selection criteria. Generating two independently selected samples of clusters, one drawn from XXL (spanning a redshift range 0.05 ≤ z ≤ 0.3) and another from GAMA (0.05 ≤ z ≤ 0.2), both spanning 0.2 ≲ M 500 ≲ 5 × 10 14  M⊙, we investigate the relationship between X-ray luminosity and velocity dispersion ( LX − σ v relation). Comparing the LX − σ v relation between the X-ray selected and optically selected samples, when not accounting for the X-ray selection, we find that the scatter of the X-ray selected sample is 2.7 times higher than the optically selected sample (at the 3.7σ level). Accounting for the X-ray selection to model the LX − σ v relation, we find that the difference in the scatter increases (with the X-ray selected sample having a scatter 3.4 times larger than the optically selected sample). Although the scatter of the optically selected sample is lower, we find 13 optically selected GAMA groups undetected in X-rays. Inspection of the difference in magnitude between the first and second brightest galaxies in the cluster, and a stacked X-ray image of these 13 groups, suggests that these are young systems still in the process of forming.